Project Gutenberg Newsletters 1999 : Thirteen Letters: December 1998 to December 1999 - Hart, Michael, 1947-2011 (Salt Lake City, UT : Project Gutenberg, 2015)
"Project Gutenberg Newsletters 1999" by Michael Hart is a collection of informative newsletters published monthly, detailing the progress and activities of Project Gutenberg during the year 1999. The newsletters likely originated in the late 20th century, a time marked by the growth of internet accessibility and digital resources. This work aims to update readers on newly available e-texts, copyright issues, and ongoing volunteer efforts to expand public domain literature. The opening of the newsletter sets the stage by introducing readers to the various sections and content that will be covered. It highlights the massive undertaking of producing and distributing a growing number of e-texts and an insightful commentary on the implications of new U.S. copyright laws. Notably, it also emphasizes Project Gutenberg's commitment to increasing accessibility to literature in multiple languages and the importance of volunteer involvement in this effort. The tone is both informative and friendly, encouraging participation and collaboration among readers and volunteers. (This is an automatically generated summary.)
Release date is 2015-04-22
Produced by David Widger
Keywords: Project Gutenberg